Sex and Experience: Modeling the Public’s Perceptions of Justice, Satisfaction, and Attitude Toward the Courts - Higgins, George E. (American journal of criminal justice, 2009)
The purpose of the present study is to examine the influence that sex has on the interconnection between justice, satisfaction with the courts, and attitudes toward the courts. Using national level polling data, the results show that different forms of justice coalesce into a latent measure of justice. Further, the results show that sex differences in our latent measure of justice do exist. In addition, those with experience with the course have a negative attitude toward the court system. Finally, the results show that the impact of justice on attitude toward the court system is partially mediated by satisfaction with the court. Policy implications are discussed.